Directed organization of gold nanoclusters on silver nanowires: a step forward in heterostructure assembly - Sharma, J.; Vivek, J. P.; Vijayamohanan, K. P.; Singh, P.; Dharmadhikari, C. V. (Applied Physics Letters, 2006)
We investigate the directed assembly of tridecylamine protected gold nanoclusters of 4-5 nm size on functionalized silver nanowires of 55-60 nm diameter and the electron transfer behavior of this integrated structure using transmission electron microscopy, non-contact atomic force microscopy, and scanning tunneling microscopy/spectroscopy. Linear I-V for bare silver nanowire suggests metallic behavior but high tunnel resistance indicates presence of insulating layer on the surface. Identical I-Vs obtained for isolated gold nanoparticle and heterostructure suggests that electron transport across nanowires in the latter is governed by gold nanoparticles in contrast to expected ballistic or diffusive transport along their length.(c) 2006 American Institute of Physics.